Histamine induced high mobility group box-1 release from vascular endothelial cells through H1 receptor - Gao, Shangze; Liu, Keyue; Ku, Wenhan; Wang, Dengli; Wake, Hidenori; Qiao, Handong; Teshigawara, Kiyoshi; Nishibori, Masahiro (Frontiers in Immunology, 2022)
Background Systemic allergic reaction is characterized by vasodilation and vascular leakage, which causes a rapid, precipitous and sustained decrease in arterial blood pressure with a concomitant decrease of cardiac output. Histamine is a major mediator released by mast cells in allergic inflammation and response. It causes a cascade of inflammation and strongly increases vascular permeability within minutes through its four G-protein-coupled receptors (GPCRs) on endothelial cells. High mobility group box-1 (HMGB1), a nonhistone chromatin-binding nuclear protein, can be actively secreted into the extracellular space by endothelial cells. HMGB1 has been reported to exert pro-inflammatory effects on endothelial cells and to increase vascular endothelial permeability. However, the relationship between histamine and HMGB1-mediated signaling in vascular endothelial cells and the role of HMGB1 in anaphylactic-induced hypotension have never been studied. Methods and results EA.hy 926 cells were treated with different concentrations of histamine for the indicated periods. The results showed that histamine induced HMGB1 translocation and release from the endothelial cells in a concentration- and time-dependent manner. These effects of histamine were concentration-dependently inhibited by d-chlorpheniramine, a specific H1 receptor antagonist, but not by H2 or H3/4 receptor antagonists. Moreover, an H1-specific agonist, 2-pyridylethylamine, mimicked the effects of histamine, whereas an H2-receptor agonist, 4-methylhistamine, did not. Adrenaline and noradrenaline, which are commonly used in the clinical treatment of anaphylactic shock, also inhibited the histamine-induced HMGB1 translocation in endothelial cells. We therefore established a rat model of allergic shock by i.v. injection of compound 48/80, a potent histamine-releasing agent. The plasma HMGB1 levels in compound 48/80-injected rats were higher than those in controls. Moreover, the treatment with anti-HMGB1 antibody successfully facilitated the recovery from compound 48/80-induced hypotension. Conclusion Histamine induces HMGB1 release from vascular endothelial cells solely through H1 receptor stimulation. Anti-HMGB1 therapy may provide a novel treatment for life-threatening systemic anaphylaxis.